COMPETITIVE ADVANTAGE AND BUSINESS PERFORMANCE: SURVIVING COVID-19 (AN EMPIRICAL STUDY ON PUBLISHING COMPANIES IN WEST JAVA, INDONESIA): (AN EMPIRICAL STUDY ON PUBLISHING COMPANIES IN WEST JAVA, INDONESIA) - Judith Gallena Sinaga; Hamfri Djajadikerta; Sylvia Fettry (Program Studi Magister Manajemen Universitas Advent Indonesia, 2025)
The aim of this study is to examine the factors affecting competitive advantage and its relationship with business performance. This study further aims to address how the publishing companies survive the pandemic Covid-19. Questionnaires were distributed to the 310 employees of publishing association and purposive sampling was employed in determining and selecting the samples (respondents). Data gathered were processed by using PLS-SEM. The results showed that publishing companies survived the crisis irrespective of the limited amount of income generated. For its significance, internal control system is significantly associated with competitive advantage while quality cost is significantly associated with business performance and competitive advantage. On another note, internal control system and competitive advantage are not significantly associated with business performance. The significance posits that quality cost is preferred to maintain for better business performance rather than focusing on internal control system and competitive advantage